Dampak Penanganan Pandemi Covid-19 terhadap Pendapatan Asli Daerah (PAD) pada Sektor Pariwisata Kota Padang - Sarah Khairani, Mai; Adnan, M. Fachri (Policy, Law and Political Research Center, 2023)
This research purpose to analyze the impact of handling the Covid-19 pandemic on Regional Original Revenue (PAD) in the Tourism sector in Padang City. The method used in this research was descriptive qualitative. In this study using source triangulation techniques in testing the validity of the data. The results of this study indicate that the policy for handling the Covid-19 pandemic has a negative impact on Regional Original Income (PAD). This was caused by a decrease in the number of tourists visiting the city of Padang in 2020 by 53% and with the handling of the Covid-19 pandemic limiting the activities of the tourism industry sector which had an impact on local tax revenue originating from the tourism sector, the hospitality industry which in 2020 was a decrease of 49% from the previous year followed by the restaurant industry by 31%, and entertainment taxes decreased from 2020-2021 by 23.39% and levies decreased by 2% during 2020-2021. In this study, it can be concluded that the policy for handling the Covid-19 pandemic has a negative impact on the tourism sector and local revenue in the city of Padang. Therefore, there is a need for an appropriate strategy to overcome this negative impact and strengthen the tourism sector in the city of Padang so that it can increase local revenue in the tourism sector.